1989
DOI: 10.1128/aac.33.9.1553
|View full text |Cite
|
Sign up to set email alerts
|

In vitro bactericidal activities of gentamicin, cefazolin, and imipenem in peritoneal dialysis fluids

Abstract: Continuous ambulatory peritoneal dialysis is an important modality of therapy for patients with renal disease. However, peritonitis continues to be a major risk factor and is usually treated by intraperitoneal administration of antimicrobial agents. Few data are available concerning the stability of antimicrobial agents in peritoneal dialysis solution beyond 48 h. Our investigation was designed to establish the chemical and biological stability of gentamicin alone and in combination with cefazolin in peritonea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…It is well known that isolates from CAPD patients with peritonitis often grow poorly or not at all in the fresh acidic dialysis fluid that is instilled into the peritoneal cavity (11,14). Furthermore, the composition of this fluid changes rapidly during dialysis, and so many workers have instead used PUD as a culture medium (8)(9)(10)(11)(12)(13)(14)16). The pH of PUD quoted in these references ranged from 7.0 to 8.6.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is well known that isolates from CAPD patients with peritonitis often grow poorly or not at all in the fresh acidic dialysis fluid that is instilled into the peritoneal cavity (11,14). Furthermore, the composition of this fluid changes rapidly during dialysis, and so many workers have instead used PUD as a culture medium (8)(9)(10)(11)(12)(13)(14)16). The pH of PUD quoted in these references ranged from 7.0 to 8.6.…”
Section: Discussionmentioning
confidence: 99%
“…The pH of PUD quoted in these references ranged from 7.0 to 8.6. In addition, some workers have centrifuged, filtered, or acidified the fluid prior to use (9)(10)(11)(12)14). In no case was it reported that increased levels of carbon dioxide were used during culture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, there is evidence in vitro that antibiotic activity is different in dianeal fluid than in standard broth. Significant impairment in the activities of aminoglycosides, fluoroquinolones, cephalosporins, and vancomycin has been shown in the comparison of MICs and minimum bactericidal concentrations in dianeal fluid to standard broth (12,28,30,31,33).…”
Section: Discussionmentioning
confidence: 99%